Clinical characteristics of asymptomatic and symptomatic patients with mild COVID-19. (July 2020) - Kim, G.-u.; Kim, M.-J.; Ra, S.H.; Lee, J.; Bae, S.; Jung, J.; Kim, S.-H.
Abstract: Objectives: Detailed knowledge on the prevalence of asymptomatic cases of coronavirus disease 2019 (COVID-19) and the clinical characteristics of mild COVID-19 is essential for effective control of the COVID-19 pandemic. We determined the prevalence of asymptomatic cases of COVID-19 and characterized the symptoms of patients with mild COVID-19. Methods: Study participants were recruited from a community facility designated for the isolation of patients without moderate-to-severe symptoms of COVID-19 in South Korea. The prevalence of asymptomatic patients at admission and the detailed symptoms of mild COVID-19 were evaluated through a questionnaire-based survey. Diagnosis of COVID-19 was confirmed by real-time RT-PCR. Results: Of the 213 individuals with COVID-19, 41 (19.2%) were asymptomatic until admission. Among the remaining patients with mild COVID-19, the most common symptom was cough (40.1%; 69/172), followed by hyposmia (39.5%; 68/172) and sputum (39.5%; 68/172). Of the 68 individuals with hyposmia, 61 (90%) had accompanying symptoms such as hypogeusia, nasal congestion or rhinorrhoea. Fever (>37.5°C) was only observed in 20 (11.6%) individuals. Conclusions: As much as one-fifth of individuals with COVID-19 remained asymptomatic from exposure to admission. Hyposmia was quite frequent among individuals with mild COVID-19, but fever was not. Social distancing should be strongly implemented to prevent disease transmission from asymptomatic individuals or those with mild and inconspicuous symptoms.